Intraperitoneal Oxygen/Ozone Treatment Decreases the Formation of Experimental Postsurgical Peritoneal Adhesions and the Levels/Activity of the Local Ubiquitin-Proteasome System - Clara Di Filippo; Annalisa Capuano; Barbara Rinaldi; Margherita Luongo; Biagio Lettieri; Francesco Rossi; Michele D'Amico (Mediators of Inflammation)
We have investigated whether an oxygen/ozone (95%O2/5%O3) mixture would have potential against the formation of experimental postsurgical peritoneal adhesions. In two groups of rats, one control intraperitoneally injected with 3 mL/rat of O2 and one intraperitoneally injected with oxygen/ozone mixture (3 mL/rat equivalent to 300 μg/kg ozone), we induced a midline laparotomy and an enterotomy at the level of the ileum to encourage the formation of peritoneal adhesions. Samples were taken from the parietal peritoneal tissue to assess the formation of adhesions 0 and 10 days after the surgical procedure and to assess the levels of ubiquitin and 20S proteasome. We found decreased formation of postsurgical peritoneal adhesions after treatment of the rats with 300 μg/kg ozone associated with a decreased levels of ubiquitin and 20S proteasome subunit within the adhered tissue. Oxygen/ozone mixture is potentially useful for approaching the post-surgical peritoneal adhesions, and the UPS system is involved in this.